2022
DOI: 10.3389/fimmu.2022.924178
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Lam. Peptide Remodels Intestinal Mucosal Barrier by Inhibiting JAK-STAT Activation and Modulating Gut Microbiota in Colitis

Abstract: Ulcerative colitis is a chronic inflammatory bowel disease (IBD), but progress in exploring its pathogenesis and finding effective drugs for its prevention and treatment has stalled in recent years. The seeds of Moringa oleifera Lam. are rich in proteins known to have multiple physiological activities. In our earlier work, we had isolated and purified a peptide (MOP) having the sequence KETTTIVR, from M. oleifera seeds; however, its anti-inflammatory activity and mechanism in vivo were unclear. Here we used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
2
8
0
Order By: Relevance
“…Additionally, administration reduced tissue MPO activity and serum LPS levels in the DSS + MOLP-M and DSS + MOLP-H groups when compared to the DSS group. This is in line with the results of Hong et al ( 27 ), which indicated that a high dose of (MOP) decreased MPO in the serum of DSS-induced UC mice. These findings suggest that MOLP plays a protective role against DSS-induced UC by inhibiting MPO activity and serum LPS levels.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, administration reduced tissue MPO activity and serum LPS levels in the DSS + MOLP-M and DSS + MOLP-H groups when compared to the DSS group. This is in line with the results of Hong et al ( 27 ), which indicated that a high dose of (MOP) decreased MPO in the serum of DSS-induced UC mice. These findings suggest that MOLP plays a protective role against DSS-induced UC by inhibiting MPO activity and serum LPS levels.…”
Section: Resultssupporting
confidence: 92%
“…And also neutrophils are one of the infiltrating cells that cause inflammation in colitis ( 26 ). This is consistent with the findings of Hong et al ( 27 ), which indicated that a high dose of (MOP) extracted and purified a peptide from M. oleifera seeds significantly reduced such mucosal damage (including the greater crypt depth), decreased in goblet cells and inflammatory cell infiltration, leading to lower histological scores in DSS-induced UC mice. Therefore, these results showed that MOLP supplementation could improve the histopathological changes in DSS-induced UC.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…seeds improved the pathological phenotype and inflammation in colitis mice by inhibiting the JAK/STAT signaling pathway. 30 Integrity of the intestinal barrier plays an important role in inhibiting NF-κB signaling activation. The study has demonstrated that enhancing intestinal barrier integrity can lead to decreased NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the peptide KETTTIVR significantly increases the relative abundances of Lachnospira , Blautia , and Ruminococcus . 30 Bacteroides , Blautia , and Lachnospiraceae_NK4A136 are genera of probiotics that produce short-chain fatty acids, which regulate host health and alleviate inflammatory diseases. 37 In comparison with the DSS group, TPGAFF intervention led to a notable increase of Bacteroides , Blautia , and Lachnospiraceae_NK4A136 .…”
Section: Discussionmentioning
confidence: 99%